Kinetic Model and Simulation Analysis for Propane Dehydrogenation in an Industrial Moving Bed Reactor - Chin, S. Y.; Radzi, S. N. R.; Maharon, I. H.; Shafawi, M. A. (waset, 2011)

(untitled)
A kinetic model for propane dehydrogenation in an industrial moving bed reactor is developed based on the reported reaction scheme. The kinetic parameters and activity constant are fine tuned with several sets of balanced plant data. Plant data at different operating conditions is applied to validate the model and the results show a good agreement between the model predictions and plant observations in terms of the amount of main product, propylene produced. The simulation analysis of key variables such as inlet temperature of each reactor (T ) and hydrogen to total hydrocarbon ratio (H2/THC) affecting process performance is performed to identify the operating condition to maximize the production of propylene. Within the range of operating conditions applied in the present studies, the operating condition to maximize the propylene production at the same weighted average inlet temperature (WAIT) is ΔT = -2, ΔT inrx1 = +1, ΔT inrx2 inrx = +1 , ΔT inrx4 inrx3 = +2 and ΔH2/THC= -0.02. Under this condition, the surplus propylene produced is 7.07 tons/day as compared with base case.